Training in Making Bouquets from Waste Paper as a Way to Foster Entrepreneurship Among Students - Harjun Harjun; Muhammad Juwantho Lewa; Siti Hardianti; Nadhine Dwi Aura Rellya; Kristala Cinta Anindita; Dini Fitriani; Talita Fitria Salwa; Putri Khairunnisa Sao-Sao; Dimas Saputra (Jurnal Kewirausahaan dan Bisnis, 2026)
The increasing use of paper in academic activities has led to a rise in thesis revision paper waste, which has the potential to pollute the environment if not properly managed. This activity aimed to provide training for students of the Economic Education Department at Halu Oleo University in processing thesis revision paper waste into economically valuable bouquets to improve creativity and entrepreneurial spirit. The method used was training and direct practice in making bouquets from paper waste materials. The results showed that paper waste could be transformed into creative products with selling value while also increasing environmental awareness and students’ interest in entrepreneurship. Therefore, utilizing paper waste into bouquets can become a creative and economical alternative for waste management.